N-Propargylamines: versatile building blocks in the construction of thiazole cores - Arshadi, S.; Vessally, E.; Edjlali, L.; Hosseinzadeh-Khanmiri, R.; Ghorbani-Kalhor, E. (Beilstein Journal of Organic Chemistry, 2017)
Thiazoles and their hydrogenated analogues are not only key structural units in a wide variety of natural products but they also constitute important building blocks in medicinal chemistry. Therefore, the synthesis of these compounds using new protocols is always interesting. It is well known that N-propargylamines can undergo a number of cyclization reactions to produce various nitrogen-containing heterocycles. In this review, we highlight the most important developments on the synthesis of thiazole and its derivatives starting from N-propargylamines. This review will be helpful in the development of improved methods for the synthesis of natural and biologically important compounds.
Keywords: 6-endo-dig cyclization; 5-exo-dig cyclization; N-heterocycles; N-propargylamines; thiazoles